PERKEMBANGAN TEKNOLOGI PERADILAN TUN DALAM BENTUK INOVASI PUTUSAN SECARA “ONE DAY PUBLISHING” - Kusumaningsih, Rila (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The rapid advancement of technology has left its imprint on all parts of life, including the State Administrative Justice system in Indonesia. As time passes, adjustments or advancements in the legal system are required to keep up with the evolution of societal concerns. The Indonesian government announced a policy through the Supreme Court to improve the quality of the State Administrative Court by instituting a One Day Publishing, which can speed up the disclosure of case information in order to realize one of the principles of justice, namely the principle of quick justice. The larger community will have easier and faster access to decision information thanks to One Day Publishing. The research method utilized to create this publication is an empirical legal research based on secondary data consisting of both primary legal materials and secondary legal materials. Currently, state administrative courts in Indonesia have implemented the one-day publishing program, which is a leading program in developing a judicial system that is in line with the evolution of the digital world. One day publishing is one of the government's initiatives, through the Supreme Court, to modernize the administrative court process in order to provide the greatest service to the people